Study on Mechanism and Main Influencing Factors of Rockburst under Complex Conditions of Hard and Deep Overburden - Ma Xingen; Pan Jun; Zou Qinghai; Li Yongyuan; Feng Fan; Wang Huifeng; Ye Xiangping; Gong Yongchun; Mou Biao (Shock and Vibration)
Xinzhuang Coal Mine is a typical kilometer-deep rockburst mine in the Ningzheng mining area of China Huaneng Group, which is still in the capital construction period. At present, there are a few studies on the rockburst mechanism and prevention of this mine. In order to explore the occurrence mechanism and main influencing factors of rockburst under the complex geological conditions of large buried depth, thick topsoil, and hard overburden in Xinzhuang Coal Mine, this paper, based on the analysis of the basic geological data of the mine, deeply explores the comprehensive disaster factors of Xinzhuang Coal Mine; then, uses the analytic hierarchy process to carry out quantitative analysis of each disaster factor, and finally, it obtains the impact type and occurrence mechanism of the mine. Through research, it is found that the main disaster factors of Xinzhuang Coal Mine are mining depth, coal seam thickness, coal seam thickness change, tectonic stress field, hard overburden, roadway layout, bottom coal reservation, and tunneling activities. The key to the process of the rockburst disaster in Xinzhuang Coal Mine is the superimposed effect of static and dynamic loads on the roadway surrounding the rock system. The potential rockburst type during excavation and mining is the “high static and dynamic load disturbance” type.